Preliminary impact of the 1998 capital control: an analysis of GDP / Noor Zahirah Mohd Sidek - Mohd Sidek, Noor Zahirah (Research Management Institute (RMI), 2005)
The 1997 financial crisis which, later, translated into an economic crisis has brought about the implementation of capital controls as a policy response in Malaysia. In this study we examine the effectiveness of capital controls on sixteen components of GDP. Using the ARMA-intervention modeling technique, we found that half of components have positive significant post capital control impact. The components that benefited from the implementation of this policy include rubber, palm oil, food, textile, construction, wholesale and retail, transport and finance. Thus, the use of capital control did confer positive results despite the fear of certain orthodox economists.